Didactic Potential Of Digital Platforms In Developing Reading Skill: The Magic School Case (Eurasian Journal of Learning and Academic Teaching, 2026)
This article provides a comprehensive study of the didactic potential of digital educational platforms in foreign language teaching, grounded in linguodidactic approach. The study primarily focuses on examining the linguodidactic foundations of adapting authentic texts to proficiency levels within the Magic School platform and its implementation in the instructional process.